Shallow stability and parameter sensitivity analysis of soil slope with frame protection under rainfall seepage - Jifeng Lian (Nature Portfolio, 2021)
Abstract Frame protection is a commonly used solution to maintain the shallow stability of soil slope under rainfall seepage. Currently, the frame structure's design is empirical, and its theoretical analysis method considering the influence of seepage is scarce. Based on the instability model of the infinite slope, the shallow stability calculation model of soil slope under the rectangular frame protection is established in this paper. The calculation results show that it is beneficial to maintain the shallow slope stability by reducing the skeleton spacing and increasing the cross-sectional size of the frame structure. Also, geometric parameters' sensitivity analysis of the frame structure is carried out based on the orthogonal experimental design methods. Therein, an optimal scheme evaluation function was constructed to balance the relationship between the safety factor and the construction material consumption. The calculation model and results included in this paper can guide the design of the rectangular frame protection to soil slope under rainfall seepage.